The Effect of Self-Leadership on the Innovative Career Performance of Faculty Members at Tabriz University of Medical Sciences: The Mediating Role of Professional Development - Fahime Valizade Azar; Hamdullah Habibi; Behnam Talebi (Taṣvīr-i salāmat, 2023)
Extended Abstract Background. Due to the progress and expansion of medical science, innovation and promotion of community-oriented medical education has a significant impact on the quality of medical services. The existence of creativity and innovation in every field of medical education among faculty members and their innovative performance can provide a suitable platform for improving the quality of medical education. Meanwhile, self-management skills and professional development play a constructive role in improving the knowledge and skills of faculty members to achieve these goals. The research aimed to investigate the potential correlation between self-leadership and innovative job performance among the faculty members at Tabriz University of Medical Sciences, Iran. Methods. The current study employed a quantitative approach with a practical purpose. The research method was descriptive and correlational, utilizing structural equation modeling. We focused on the faculty members of Tabriz University of Medical Sciences during the academic year 2021-2022. According to the statistical resources, there were 793 faculty members at the university in the mentioned period. As per Morgan's table, the sample size consisted of 260 individuals. The methods utilized to collect the required data were the standard questionnaire of occupational innovation developed by Etlai and Akif (1982), the professional development questionnaire of faculty members developed by Davarpanah (2018), and the self-leadership questionnaire developed by Rahimi, et al. (2019). To statistically analyze the research data, the SPSS 23 software was used to verify the normality of the studied variables. To calculate the correlation coefficients between them, AMOS Ver. 23 was utilized. Results. According to the correlation matrix table, there was a direct and significant relationship between professional development, self-leadership, and inventive performance. The measurement models fit well based on the results of confirmatory factor analysis and assessment indices. The Cronbach's alpha value was 0.82. The self-leadership coefficient of influence on work innovation was 0.37, self-leadership had a 0.38 coefficient of influence on professional progress, and professional development had a 0.31 impact factor on job innovation. Conclusion. This study revealed that faculty members' self-leadership and professional development had a positive and statistically significant effect on their innovative career performance. The results also confirmed the mediating function of professional development in the relationship between self-leadership and innovative career performance.